The influence of emotional carrying capacity and network ethnic diversity on entrepreneurial self-efficacy - Golshan Javadian; Tina R. Opie; Salvatore Parise (New England Journal of Entrepreneurship (NEJE), 2018)
Purpose - One key determinant of entrepreneurial success is entrepreneurial self-efficacy (ESE), defined as an individual's confidence in his or her ability to perform entrepreneurial tasks. Whereas previous research has examined how individual and business factors influence ESE, the purpose of this paper is to analyze the influence of entrepreneurs' social networks upon ESE. The paper examines such relationships for black and white entrepreneurs. Design/methodology/approach - In total, 110 black and white entrepreneurs responded to a survey measuring ESE and critical constructs representing elements of the quality of entrepreneurs' networks: emotional carrying capacity (ECC) and network ethnic diversity. Findings - The authors found significant, positive relationships between both ECC and network ethnic diversity on ESE for white entrepreneurs but only found a significant positive relationship between ECC and ESE for black entrepreneurs. Originality/value - While research is clear about the role that ESE plays in entrepreneurial activities, few studies have focused on the factors that improve ESE. In the present work, the authors study the role of context by examining how entrepreneurs' social networks influence ESE. The authors examine such influences for both white and black entrepreneurs to better understand the implications of ethnicity.
Keywords: 650; Entrepreneurial self-efficacy; Emotional carrying capacity; High-quality connections; Network ethnic diversity